Extracellular Vesicles in Viral Replication and Pathogenesis and Their Potential Role in Therapeutic Intervention - Asit Kumar; Sunitha Kodidela; Erene Tadrous; Theodore James Cory; Crystal Martin Walker; Amber Marie Smith; Ahona Mukherjee; Santosh Kumar (Viruses, 2020)
Extracellular vesicles (EVs) have shown their potential as a carrier of molecular information, and they have been involved in physiological functions and diseases caused by viral infections. Virus-infected cells secrete various lipid-bound vesicles, including endosome pathway-derived exosomes and microvesicles/microparticles that are released from the plasma membrane. They are released via a direct outward budding and fission of plasma membrane blebs into the extracellular space to either facilitate virus propagation or regulate the immune responses. Moreover, EVs generated by virus-infected cells can incorporate virulence factors including viral protein and viral genetic material, and thus can resemble noninfectious viruses. Interactions of EVs with recipient cells have been shown to activate signaling pathways that may contribute to a sustained cellular response towards viral infections. EVs, by utilizing a complex set of cargos, can play a regulatory role in viral infection, both by facilitating and suppressing the infection. EV-based antiviral and antiretroviral drug delivery approaches provide an opportunity for targeted drug delivery. In this review, we summarize the literature on EVs, their associated involvement in transmission in viral infections, and potential therapeutic implications.